Microanatomy of the acetabular cavity and its relation to growth. - Portinaro, N; Murray, D; Benson, M (2001)
The anatomy and development of the growing acetabulum are not clearly understood. We dissected and studied histologically two acetabula from the pelvis of a three-month-old infant. Relative rates of growth at the different growth plates were assessed by comparing the height of the proliferative layer with that of the hypertrophic layer. The three bones which form the acetabulum are surrounded by growth plates on all sides except medially. These face towards the centre of the triradiate cartilage, the limbs of the triradiate cartilage and the articular surface and each may be divided into four distinct areas according to the orientation of its cell columns which reflect the direction of growth. Growth was particularly rapid at the ischial growth plates directed towards the centre and the articular cartilage, add on both sides of the anterior limb of the triradiate cartilage. These findings may explain the mechanism by which the acetabulum changes orientation and inclination with growth.